Pseudomonas aeruginosa biofilm formation: Antibiofilm Strategies and conventional methods of evaluation. (Journal of Basic and Applied Research in Biomedicine, 2024)
Pseudomonas aeruginosa is an opportunistic pathogen known for its ability to form resilient biofilms, which contribute to its persistence in chronic infections and resistance to antimicrobial agents. This review provides a detailed examination of biofilm development stages—attachment, maturation, and dissemination and highlights the role of specific genes in each stage, with a focus on quorum sensing as a key regulatory mechanism governing bacterial communication within biofilms. It also evaluates conventional methods for analyzing P. aeruginosa biofilm phenotypes, discussing their purposes, advantages, and limitations. Accordingly, future research should focus on standardizing protocols, advancing imaging technologies, and targeting biofilm-specific mechanisms. Collaborative efforts across disciplines and translational research will be essential for developing effective therapies. This review aims to deepen our understanding of P. aeruginosa biofilm dynamics and highlight the implications for developing effective therapies against biofilm-associated infections.